Automatic Detection of Depression from Text Data: A Systematic Literacture Review - Magami, Felipe Morine; Digiampietri, Luciano Antonio (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2020: Anais do XVI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2020.13752, 2020)
Depression is a mental disorder that affects hundreds of millions of people worldwide, with potentially serious consequences if left without treatment. Despite that, many people still suffer from depression without a diagnosis. Recently, the amount of studies related to the automatic detection of depression has improved. The objective of this paper is to identify the methods and techniques used by studies about depression detection through text data, by conducting a systematic review.